Literacy in Lakon Pandu Suwarga: Javanese View of Life - Syafi'i, Muhammad; Setiawan, Agus Mahfudin; Parangu, Reza Nawafella Alya (Universitas Islam Negeri Raden Intan Lampung, 2023)
Wayang kulit performances are a symbol of the drama of Javanese life. This research aims to understand Javanese cultural symbols in wayang performances, especially the play Pandu Suwarga, by using a mixed research method that combines library research and field research. The data collection technique was non-participant observation via YouTube social media and analyzed using Turner's symbol theory. The research results found that especially the Suwarga Pandu Play, contained deep moral lessons. One significant finding is the importance of filial piety to parents, which is manifested through the desire of the Five Pandavas for their parents to enter heaven. The characters in this show are symbolically divided into two main groups: good, represented by the Five Pandavas, and bad, represented by the Kauravas. Thus, this article contributes to the understanding of Javanese culture and the study of shadow puppets as a medium for storytelling and conveying life values. The symbols found in the play Pandu Suwarga provide a deep insight into the complexity of the wayang tradition and its relevance in permeating Javanese cultural values.